A novel droop coefficient to realize rapid SOC balance for distributed energy storage systems - Yuanxi Liu; Ling Yang; Maohua Wei (International Journal of Electrical Power & Energy Systems)
In the realm of isolated direct-current microgrids with varying distributed energy storage unit capacities, a new energy equalization strategy is proposed. This method involves an innovative approach that integrates an improved state-of-charge equalization control integrated with a sigmoid function to adaptively adjust the droop coefficient, aiming to accelerate the state-of-charge equalization rate. Furthermore, a virtual voltage drop equalization control is designed to dynamically adjust the output current of each distributed energy storage unit through a simple proportional–integral controller. This eliminates the influence of line impedance on accurate current distribution, improving overall accuracy. Additionally, a dynamic consistency algorithm is employed to gather average information about the distributed energy storage system, reducing communication line pressure as local nodes only exchange information with neighboring nodes. Integrating the aforementioned modules, the strategy proposed in this paper achieves rapid state-of-charge equalization, precise distribution of output current, and stable maintenance of the bus voltage. Finally, rigorous analysis of experimental results under various operating conditions verifies the feasibility and effectiveness of this control strategy by using the RT-LAB.